PERANCANGAN SISTEM INFORMASI LAPORAN HASIL TARGET PRODUKSI 6 FACTORY 3 PADA PT.DAESE GARMIN - Adriana Niis; Dwi Robiul Rochmawati (LPPM Politeknik Pajajaran ICB Bandung, 2022)
This study aims to design an information system for target results reports using PHP and My SQL at PT. Daese Garmin Bandung. The data collection method used in this study uses the direct observation method and a literature review related to the subject matter and software development methods used. used is by using a prototyping model for solving the problem. From the research conducted, there are factors that hinder the target results reporting system, which still uses manual or regular recording in a number of agenda books, which are felt to be less effective and efficient for target results reports. For the creation of an information system design for this report, the authors used an object-oriented approach using the UML (Unified Modeling Language), and implemented it using the PHP and MySQL programming languages as a DBMS (Database Management System). With the information system Report, this letter is expected to be a solution for improving the performance of report data. The suggestions given are: 1) providing training for the tasks that will run this information system; and 2) maintaining and developing a new information system for the future.